The Farnesyltransferase β-Subunit Ram1 Regulates Sporisorium scitamineum Mating, Pathogenicity and Cell Wall Integrity - Sun, Shuquan; Deng, Yizhen; Cai, Enping; Yan, Meixin; Li, Lingyu; Chen, Baoshan; Chang, Changqing; Jiang, Zide (Frontiers in Microbiology, 2019)
The basidiomycetous fungus Sporisorium scitamineum causes a serious sugarcane smut disease in major sugarcane growing areas. Sexual mating is essential for infection to the host; however, its underlying molecular mechanism has not been fully studied. In this study, we identified a conserved farnesyltransferase (FTase) β subunit Ram1 in S. scitamineum. The ram1Δ mutant displayed significantly reduced mating/filamentation, thus of weak pathogenicity to the host cane. The ram1Δ mutant sporidia showed more tolerant toward cell wall stressor Congo red compared to that of the wild-type. Transcriptional profiling showed that Congo red treatment resulted in notable up-regulation of the core genes involving in cell wall integrity pathway in ram1Δ sporidia compared with that of WT, indicating that Ram1 may be involved in cell wall integrity regulation. In yeast the heterodimeric FTase is responsible for post-translational modification of Ras (small G protein) and a-factor (pheromone). We also identified and characterized two conserved Ras proteins, Ras1 and Ras2, respectively, and a MAT-1 pheromone precursor Mfa1. The ras1Δ, ras2Δ and mfa1Δ mutants all displayed reduced mating/filamentation similar as the ram1Δ mutant. However, both ras1Δ and ras2Δ mutants were hypersensitive to Congo red while the mfa1Δ mutant was the same as wild-type. Overall our study displayed that RAM1 plays an essential role in S. scitamineum mating/filamentation, pathogenicity, and cell wall stability.